2019
DOI: 10.18488/journal.74.2019.61.57.73
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality and Outpatients Satisfaction in Public Hospitals in Malaysia

Abstract: The convenience sampling technique was used and 409 useful questionnaires were collected. The results showed that there is a significant positive relationship between Competency, Tangibility, Reliability and Outpatient Satisfaction. However, Responsiveness and Courtesy have a positive and insignificant relationship with Outpatients' Satisfaction. By determining the significant variables influencing outpatients' satisfaction, this study gives an insight for managers and staff of public hospitals on the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Teaching hospitals serve their role as constituents of a Healthcare System with a slightly nuanced set of priorities geared towards learning and teaching. On the contrary, privately owned and operated healthcare facilities are not fully integrated with the national healthcare system and operate under their own accordance, while following the rules and regulations set by their respective governing bodies [120,121]. This indicates that healthcare facilities are mandated by the regulations of their own respective governing bodies.…”
Section: Institutional Influences On Wayfinding In Healthcare Facilitiesmentioning
confidence: 99%
“…Teaching hospitals serve their role as constituents of a Healthcare System with a slightly nuanced set of priorities geared towards learning and teaching. On the contrary, privately owned and operated healthcare facilities are not fully integrated with the national healthcare system and operate under their own accordance, while following the rules and regulations set by their respective governing bodies [120,121]. This indicates that healthcare facilities are mandated by the regulations of their own respective governing bodies.…”
Section: Institutional Influences On Wayfinding In Healthcare Facilitiesmentioning
confidence: 99%
“…Service satisfaction, as a healthcare system factor, could influence the quality of care provided to the patients. There have been allegations of inadequate facilities, incompetent staff, excessive wait times, and negative attitudes in public hospitals (Ting et al, 2019 ; Garney et al, 2021 ). Inadequate healthcare services may increase the burden of care, which may have a detrimental effect on the patient’s results.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of technology-based or digital information systems is expected to assist in infection prevention and control and enhance the quality of healthcare services within a healthcare facility (LeRouge et al 2007). This, in turn, will contribute to patient satisfaction, as evidenced by research conducted by Ting et al (2019) which concluded that good service quality has a positive impact on patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%